2016
DOI: 10.1080/01419870.2017.1245430
|View full text |Cite
|
Sign up to set email alerts
|

International opportunities on the way up: alternative career paths of descendants of migrants from Turkey in the field of professional business services

Abstract: This qualitative study examines the career paths of descendants of labour migrants from Turkey in the field of professional business services. Through in-depth interviews with upwardly mobile professionals in leading positions, the article presents evidence from four countries (France, Germany, the Netherlands and Sweden). Respondents reflect on their professional career as a process constituted through personal interactions while displaying their perceptions of restrictive national conditions that affect thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Another strand of emerging research examines the "successful" group within the Turkish second generation, thereby emphasizing that the entire group cannot be categorised as disadvantaged (Crul et al 2017;Schneider and Lang 2014;Keskiner and Crul 2017;Vermeulen and Keskiner 2017). Studies pursuing a more qualitative approach have identified the roles of institutional structures in education and the labour market in shaping the upward mobility of descendants of Turkish immigrants (Keskiner and Crul 2017;Konyali 2017). While successful in uncovering the mechanisms to achieve higher education levels, this stream of research does not account for those individuals who do not achieve upward mobility, nor the type of support mechanisms available (or not) to them.…”
Section: Youth Transitions Of Descendants Of Turkish Immigrantsmentioning
confidence: 99%
“…Another strand of emerging research examines the "successful" group within the Turkish second generation, thereby emphasizing that the entire group cannot be categorised as disadvantaged (Crul et al 2017;Schneider and Lang 2014;Keskiner and Crul 2017;Vermeulen and Keskiner 2017). Studies pursuing a more qualitative approach have identified the roles of institutional structures in education and the labour market in shaping the upward mobility of descendants of Turkish immigrants (Keskiner and Crul 2017;Konyali 2017). While successful in uncovering the mechanisms to achieve higher education levels, this stream of research does not account for those individuals who do not achieve upward mobility, nor the type of support mechanisms available (or not) to them.…”
Section: Youth Transitions Of Descendants Of Turkish Immigrantsmentioning
confidence: 99%
“…As highly educated second-generation professionals are entering the labour market in increasing numbers, it is relevant to ask whether they are involved in ethnic niche formation in the upper tiers of the labour market. Studies on highly educated children of Turkish migrants in Europe reveal that they occasionally try to capitalize on their ethnic background to establish their own businesses or create niches within mainstream firms where they can use their ethnic background as a resource, partly as a response to blocked opportunities and subtle forms of discrimination (Waldring, Crul, and Ghorashi 2015;Konyali 2017;Keskiner and Crul 2017;. This strand of literature is concerned with individual adaptations and strategies, and suggests that some ethnic minority individuals are able to capitalize on their minority background in the labour market.…”
Section: Ethnic Niches In the Labour Marketmentioning
confidence: 99%
“…However, the few business professionals in the study who work directly with clients or markets in their parents' country of origin experience their cultural competence being recognized as an asset (cf. Konyali 2017). Thus, in business and finance, ethnicity appears to be recognized and used as a resource only if it is directly relevant to the client base or targeted markets.…”
Section: Ethnic Niches In the Mainstream Business Sectormentioning
confidence: 99%
See 2 more Smart Citations